Outcomes and survival analysis of old‐to‐old simultaneous pancreas and kidney transplantation. (3rd July 2013) - Kayler, Liise K.; Wen, Xuerong; Zachariah, Mareena; Casey, Michael; Schold, Jesse; Magliocca, Joseph
Summary: Outcomes of old‐donor simultaneous pancreas–kidney transplantation (SPKT) have not been thoroughly studied. Scientific Registry of Transplant Recipients data reported for SPKT candidates receiving dialysis wait‐listed between 1993 and 2008 ( n = 7937) were analyzed for outcomes among those who remained listed ( n = 3301) and of SPKT recipients ( n = 4636) using multivariable time‐dependent regression models. Recipients were stratified by donor/recipient age (cutoff 40 years) into: young‐to‐young ( n = 2099), young‐to‐old ( n = 1873), old‐to‐young ( n = 293), and old‐to‐old ( n = 371). The overall mortality was 12%, 14%, 20%, and 24%, respectively, for those transplanted, and 50% for those remaining on the waiting list. On multivariable analysis, old‐donor SPKT was associated with significantly higher overall risks of patient death, death‐censored pancreas, and kidney graft failure in both young (73%, 53%, and 63% increased risk, respectively) and old (91%, 124%, and 85% increased risk, respectively) recipients. The adjusted relative mortality risk was similar for recipients of old‐donor SPKT compared with wait‐listed patients including those who subsequently received young‐donor transplants (aHR 0.95; 95% CI 0.78, 1.12) except for candidates in OPOs with waiting times ≥604 days (aHR 0.65, 95% CI 0.45–0.94). Old‐donor SPKT results in significantly worse graft survival and patient mortality without any waiting‐time benefit as compared to young‐donor SPKT, except for candidates with expected long waiting times.